European modernity and the Arab Mediterranean : toward a new philology and a counter-orientalism - Mallette, Karla (University of Pennsylvania Press, 2010)
Mallette examines Orientalist philology in southern Europe produced between the mid-nineteenth and mid-twentieth century. Focusing on Italy, Spain, and Malta, she conducts close comparative readings of a wide range of philological narratives to reveal the influences Arab and Islamic traditions have had on the development of modern European culture.